Construction of a Topological Group Based on Elliptic Functions - Mohammed, Nafya H. (Sulaimani Journal for Pure and Applied Sciences, 2010)
The aim of this paper is the construction of a topological group; for this purpose we have taken a space whose elements are elliptic functions (doubly periodic meromorphic functions). And we have focused on the set of all elliptic functions of the same periods.
Keywords: Elliptic Function; Topological Space; Topological Group